ANALYSING THE ALIGNMENT OF LOTS AND HOTS IN SUMMATIVE ASSESSMENTS WITHIN THE MERDEKA CURRICULUM - Bajo, Simforianus Mario (Journal of Language, Literature and Teaching, 2025)
This study examines the alignment of Lower Order Thinking Skills (LOTS) and Higher Order Thinking Skills (HOTS) in summative assessments within the context of the Merdeka curriculum at SMP Amore Prime School. The research utilizes a descriptive quantitative approach, analyzing English assessment items for grade 8 students in the 2024-2025 academic year. Data was collected from 51 summative test items, categorized according to Bloom’s revised taxonomy, with a focus on the distribution of LOTS and HOTS. The findings reveal a dominance of LOTS-based items (70.6%) over HOTS-based items (29.4%), indicating a gap in the ideal implementation of the Merdeka curriculum, which emphasizes critical thinking, creativity, and independent learning. Although the assessment items reflect an attempt to integrate both cognitive levels, the imbalance suggests that traditional rote-learning practices still prevail, particularly in assessing foundational knowledge. This study highlights the need for greater emphasis on HOTS in language assessments to fully align with the goals of the Merdeka curriculum and support the development of students' critical thinking and problem-solving skills.